대학 비대면 교양수업에 대한 교수와 학생의 인식 차이 및 수업만족도에 미치는 영향에 관한 연구 - 서일보(Seo, Il Bo) (교양교육연구, 2021)
본 연구에서는 대학의 비대면 교양수업을 경험한 교수와 학생들을 대상으로 교육 실태 및 수업만족도 에 미치는 요인을 파악하여 향후 온라인 교육의 질적 개선을 위한 시사점을 도출하였다. 이를 위해 비대면 교양수업을 운영한 경험이 있는 교수 81명과 수강한 경험이 있는 재학생 560명을 연구대상으로 연구를 진행하였다. 연구내용은 학습경험, 몰입도, 성취도, 수업만족도, 지속수강의도, 그리고 향후 비대면 교육의 개선을 위한 보완점에 대해서 조사하였다. 설문 분석 결과 첫째, 학습경험의 수업내용과 평가, 몰입도, 성취도, 수업만족도에서 교수와 학생 간 통계적 유의한 차이를 보였으며, 요인 중 평가를 제외하고 학생이 교수에 비해 비대면 교양수업에 대해 긍정적인 인식을 갖고 있는 것으로 나타났다. 둘째, 전반적인 만족도에 영향을 주는 요인을 도출하기 위해 교수와 학생 각각 다중회귀분석을 진행하였 다. 그 결과 교수자의 경우 수업만족도에 유의한 영향을 미치는 요인은 성취도, 상호작용으로 도출되었고 학생은 몰입도, 상호작용이 통계적으로 유의한 영향을 미치는 것으로 확인되었다. 셋째, 교수와 학생의 비대면 교양수업의 보완사항으로 교수는 상호작용이 결여된 수업 지행, 학생은 영상콘텐츠의 질 개선을 요구했다. 본 연구에서는 이상의 결과를 종합하여 향후 비대면 교양 수업 개선을 위한 시사점과 후속 연구를 제언하였다. In this study, implications for improving the quality of online education in the future were derived by identifying the factors affecting the educational status and class satisfaction of professors and students who have experienced non-face-to-face liberal arts classes at universities. For this purpose, 81 professors who have experience running non-face-to-face liberal arts classes and 560 current students who have taken such classes were the research subjects. As for the contents of the study, the learning experience, immersion, achievement, class satisfaction, continuing course intent, and supplementary points for the improvement of non-face-to-face education in the future were investigated. As a result of the survey analysis, first, there were statistically significant differences between professors and students regarding class content, evaluation, immersion, achievement, and class satisfaction of the learning experience. appeared to have a positive perception (who appeared to have this perception?) Second, multiple regression analysis was performed for each professor and student to derive factors affecting overall satisfaction. As a result, in the case of instructors, factors that had a significant effect on class satisfaction were derived from achievement and interaction, and for students, this study confirmed that the degree of immersion, and interaction had a statistically significant effect. Third, as a complement to non-face-to-face liberal arts classes between professors and students, the professors demanded that the classes be conducted without interaction, whereas the students demanded improvement in the quality of video content. In this study, by synthesizing the above results, implications and follow-up studies were suggested for the improvement of non-face-to-face liberal arts classes in the future. KCI Citation Count: 12